Azwar Anas and Innovation in Local Government: A Phronesis Leadership Study - Bima Katangga (Indonesian Association for Public Administration (IAPA), 2019)
Phronesis leadership is the extraction of Aristotle's philosophy which involves judgment from the individual leader in determining the good value of reality. This article aims to analyze leadership practice in developing countries, qualitatively using 6 criteria of Nonaka's et al (2018) frameworks. The purpose of this article is to find out how Azwar Anas's phronesis leadership in Banyuwangi, Indonesia, can produce service innovations such as the